Professional journal in the system of scientific knowledge - Veniamin V. Simonov (Российский журнал истории Церкви)
The purpose of the article is to determine the place of the new professional journal on the history of the Church offered to the reader in the flow of special literature, taking into account the current state of humanitarian knowledge in the context of globalization and the systemic crisis of institutional Christianity.